2000
DOI: 10.1073/pnas.030545097
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of tumor necrosis factor-related apoptosis-inducing ligand and ionizing radiation in breast cancer therapy

Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is a potent endogenous activator of the cell death pathway and functions by activating the cell surface death receptors 4 and 5 (DR4 and DR5). TRAIL is nontoxic in vivo and preferentially kills neoplastically transformed cells over normal cells by an undefined mechanism. Radiotherapy is a common treatment for breast cancer as well as many other cancers. Here we demonstrate that ionizing radiation can sensitize breast carcinoma cells to TRAIL-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
325
3
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 480 publications
(343 citation statements)
references
References 41 publications
13
325
3
2
Order By: Relevance
“…The most commonly described mechanism of sensitization to TRAIL by drugs and irradiation is up-regulation of TRAIL-R2 and, less commonly, TRAIL -R1. 8,9,16,29,36,39 This mechanism is not operative in the cooperation between TRAIL and TK /GCV in the SH -EP cells studied because no up -regulation was observed following TK /GCV. TRAIL -R2 is a target gene of p53; 41,52 thus, p53 mutations may abrogate up -regulation of TRAIL -R2 following TK /GCV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly described mechanism of sensitization to TRAIL by drugs and irradiation is up-regulation of TRAIL-R2 and, less commonly, TRAIL -R1. 8,9,16,29,36,39 This mechanism is not operative in the cooperation between TRAIL and TK /GCV in the SH -EP cells studied because no up -regulation was observed following TK /GCV. TRAIL -R2 is a target gene of p53; 41,52 thus, p53 mutations may abrogate up -regulation of TRAIL -R2 following TK /GCV.…”
Section: Discussionmentioning
confidence: 99%
“…8,16 SH -EP cells express little TRAIL -R1, but abundant TRAIL -R2, on the cell surface ( data not shown ). However, cell surface expression of TRAIL-R1 and TRAIL -R2 was not induced following TK / GCV (data Cancer Gene Therapy TRAIL enhances TK/GCV gene therapy of neuroblastoma C Beltinger et al Cancer Gene Therapy TRAIL enhances TK/GCV gene therapy of neuroblastoma C Beltinger et al not shown ).…”
Section: Tk / Gcv Does Not Increase Trail -R1 and Trail -R2mentioning
confidence: 91%
“…To overcome this resistance, TRAIL-induced signaling is being studied alone or in combination with different sensitizing agents, such as chemotherapeutic drugs, cytokines and inhibitors of survival pathways [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Targeting TRAIL-receptor mediated signaling pathways for induction of apoptosis is currently under evaluation in multiple clinical trials for several types of cancer [7,8]. Finally, combined modality treatments, which include γ-irradiation and specific inhibitions of the cell survival pathways, appear to be promising approaches for the control and suppression of cancer development [9,10].…”
Section: Introductionmentioning
confidence: 99%